Yeast RHO3 and RHO4 ras superfamily genes are necessary for bud growth, and their defect is suppressed by a high dose of bud formation genes CDC42 and BEM1. - Yasuji Matsui; Akio Toh‐e (1992)
RHO3 and RHO4 are members of the ras superfamily genes of the yeast Saccharomyces cerevisiae and are related functionally to each other. Experiments using a conditionally expressed allele of RHO4 revealed that depletion of both the RHO3 and RHO4 gene products resulted in lysis of cells with a small bud, which could be prevented by the presence of osmotic stabilizing agents in the medium. rho3 rho4 cells incubated in medium containing an osmotic stabilizing agent were rounded and enlarged and displayed delocalized deposition of chitin and delocalization of actin patches, indicating that these cells lost cell polarity. Nine genes whose overexpression could suppress the defect of the RHO3 function were isolated (SRO genes). Two of them were identical with CDC42 and BEM1, bud site assembly genes involved in the process of bud emergence. A high dose of CDC42 complemented the rho3 defect, whereas overexpression of RHO3 had an inhibitory effect on the growth of mutants defective in the CDC24-CDC42 pathway. These results, along with comparison of cell morphology between rho3 rho4 cells and cdc24 (or cdc42) mutant cells kept under the restrictive conditions, strongly suggest that the functions of RHO3 and RHO4 are required after initiation of bud formation to maintain cell polarity during maturation of daughter cells.